Structural insight into the mechanism of energy transfer in cyanobacterial phycobilisomes - Lvqin Zheng; Zhenggao Zheng; Xiying Li; Guopeng Wang; Kun Zhang; Peijun Wei; Jindong Zhao; Ning Gao (2021)
Abstract Phycobilisomes (PBS) are the major light-harvesting machineries for photosynthesis in cyanobacteria and red algae and they have a hierarchical structure of a core and peripheral rods, with both consisting of phycobiliproteins and linker proteins. Here we report the cryo-EM structures of PBS from two cyanobacterial species, Anabaena 7120 and Synechococcus 7002. Both PBS are hemidiscoidal in shape and share a common triangular core structure. While the Anabaena PBS has two additional hexamers in the core linked by the 4th linker domain of ApcE (L CM ). The PBS structures predict that, compared with the PBS from red algae, the cyanobacterial PBS could have more direct routes for energy transfer to ApcD. Structure-based systematic mutagenesis analysis of the chromophore environment of ApcD and ApcF subunits reveals that aromatic residues are critical to excitation energy transfer (EET). The structures also suggest that the linker protein could actively participate in the process of EET in both rods and the cores. These results provide insights into the organization of chromophores and the mechanisms of EET within cyanobacterial PBS.